Comparative and evolutionary analyses of Meloidogyne spp. based on mitochondrial genome sequences - Garcia, Laura Evangelina (2015)
Molecular taxonomy and evolution of nematodes have been recently the focus of several studies. Mitochondrial sequences were proposed as an alternative for precise identification of Meloidogyne species, to study intraspecific variability and to follow maternal lineages. We characterized the mitochondrial genomes (mtDNAs) of the root knot nematodes M. floridensis, M. hapla and M. incognita. These were AT rich (81?83%) and highly compact, encoding 12 proteins, 2 rRNAs, and 22 tRNAs. Comparisons with published mtDNAs of M. chitwoodi, M. incognita (another strain) and M. graminicola revealed that they share protein and rRNA gene order but differ in the order of tRNAs. The mtDNAs of M. floridensis and M. incognita were strikingly similar (97-100% identity for all coding regions). In contrast, M. floridensis, M. chitwoodi, M. hapla and M. graminicola showed 65-84% nucleotide identity for coding regions. Variable mitochondrial sequences are potentially useful for evolutionary and taxonomic studies. We developed a molecular taxonomic marker by sequencing a highly-variable ~2 kb mitochondrial region, nad5-cox1, from 36 populations of root-knot nematodes to elucidate relationships within the genus Meloidogyne. Isolates of five species formed monophyletic groups and showed little intraspecific variability. We also present a thorough analysis of the mitochondrial region cox2-rrnS. Phylogenies based on either mitochondrial region had good discrimination power but could not discriminate between M. arenaria, M. incognita and M. floridensis.